Analisis Tingkat Kepuasan Pasien Rawat Inap BPJS Terhadap Mutu Pelayanan Kesehatan Pada Rumah Sakit Tipe C - Viva Maiga Mahliafa Noor; Feny Tunjungsari; Hawin Nurdiana; Muchammad Arif Fanani (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2022)
The quality of health services is the degree of perfection of health services in accordance with professional standards and service standards. The quality of health services can be measured by five quality dimensions, namely reliability, assurance, tangible, empathy, responsiveness. The ultimate goal of the quality of health services is the creation of patient satisfaction. This study aims to determine the relationship between the quality of health services and the satisfaction of inpatients class III JKN participants at Prof. Dr. Soekandar Hospital at Mojosari. The research design is analytical observational with a cross sectional approach. The sample is 201 inpatients. Hypothesis testing using Kendall's tau test. Based on the results of the analysis, it was found that p = 0.000 which stated that there was a relationship between the quality of health services and the satisfaction of class III inpatients of JKN participants. This shows that the quality of health services greatly affects the satisfaction of inpatients. If the quality of health services provided is good, the patient will feel satisfied. The study concluded that there was a relationship between the quality of health services and the level of satisfaction of inpatients. Good service quality will result in a high level of satisfaction.